Monitoring systemic risk in the hedge fund sector. Issue 12 (2nd December 2017) - Hespeler, Frank; Loiacono, Giuseppe
Abstract : We propose measures for systemic risk generated through intra-sectorial interdependencies in the hedge fund sector. These measures are based on variations in the average cross-effects of funds showing significant interdependency between their individual returns and the moments of the sector's return distribution. The proposed measures display a high ability to identify periods of financial distress, are robust to modifications in the underlying econometric model and are consistent with intuitive interpretation of the results.